MERETAS AKTUALITAS ISLAMIC SOCIAL REPORT: SEBAGAI CORPORATE SOCIAL RESPONSIBILITIES FRAMING BERBASIS SYARIAH (DALAM PENDEKATAN FILOSOFIS) - Cahya, Bayu Tri; Hanifah, Umi (Universitas Islam Negeri Sunan Kudus, 2016)
This article analysed the concept of islamic social developmentreport as a frame of sharia-based corporate socialresponsibilities. The study was conducted by library researchbased on previous studies and related literature. The resultsindicated that the concept of social islamic report was based onthe philosophy of good governance and corporate socialperformance reporting standard that takes into account theaspects of material, moral, and spiritual in reporting. Inparticular, this index is an extension of social performancereporting standards which include society's expectations notonly about the role of corporations in the economy, but also thecompany's role in the spiritual perspective. Besides the indexalso places emphasis on social justice related to theenvironment, the rights of minorities, and employees.Finally,syariah framework is part of a corporate strategy aimed at thesustainability of the company, providing benefits to thecommunity and participate in the social interest.